2005
DOI: 10.1177/0020764005053267
|View full text |Cite
|
Sign up to set email alerts
|

Social Services and Health Services Day Care in Mental Health: The Social Networks and Care Needs of their Users

Abstract: It is vital to understand differences between health service day hospitals and social service day centres given the increasing integration of health and social care. The present study shows that the two user groups are significantly different. It is unlikely that the needs of most day care users could be met by either service interchangeably.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 23 publications
1
25
0
6
Order By: Relevance
“…Although psychosocial functioning showed a bivariate association with social network in the present study it was not significant in any of the regression analyses, which indicates that other predictors were more important. The main explanation may instead be that participants in consumer-run community mental health programmes tend to report larger and more diverse social networks as opposed to users of DCs and day hospitals (Catty et al, 2005a;Hardiman & Segal, 2003). Although the clubhouses are not consumer-run they are strongly consumer-centred (Bellamy at al., 2006) and this approach and the emphasis on peer support probably facilitate the making of friends and strengthen one's network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although psychosocial functioning showed a bivariate association with social network in the present study it was not significant in any of the regression analyses, which indicates that other predictors were more important. The main explanation may instead be that participants in consumer-run community mental health programmes tend to report larger and more diverse social networks as opposed to users of DCs and day hospitals (Catty et al, 2005a;Hardiman & Segal, 2003). Although the clubhouses are not consumer-run they are strongly consumer-centred (Bellamy at al., 2006) and this approach and the emphasis on peer support probably facilitate the making of friends and strengthen one's network.…”
Section: Discussionmentioning
confidence: 99%
“…Research comparing users of day centres with those attending day hospitals has shown, however, that the former reported more social interaction (Catty, Goddard, & Burns, 2005a) and were more likely to confide in friends and neighbours than in professionals (Catty, Goddard, White, & Burns, 2005b). A Swedish study showed that social support was mainly provided by informal caregivers, for example, family members.…”
Section: Social Network Among Users Of Clubhouses and Day Centresmentioning
confidence: 99%
“…44,45 Other research acknowledged that the nature of networks and their quality were as crucial as size. 46 While there may be potential benefits from larger social networks, we note the potential for negative effects of social relationships. We need to treat with caution the idea that larger social networks are a desirable and manageable outcome for all individuals.…”
Section: Approach To Literature Reviewingmentioning
confidence: 99%
“…This finding has been replicated in studies which had also reported a lack of social support, and unmet needs around social interaction and community belonging. 82,83 Studies which examined composition of social networks of individuals with psychosis had found them to contain fewer friends 46 and more service practitioners 84 than the general population, and the onset of psychosis can involve changes in social networks and the loss of friends. 85 It is the multifaceted and dynamic nature of social networks that this study explores, looking beneath a map of connections to understand the negotiated meaning, sets of choices, capacity for growth and qualities such as reciprocity.…”
Section: The Recovery Approachmentioning
confidence: 99%
“…Community-based day centers (DCs) form a common alternative for people with psychiatric disabilities in order to break isolation due to mental illness and become more engaged in occupations (Bejerholm & Eklund, 2006;Bryant, 2009;Catty, Goddard, & Burns, 2005a).…”
Section: Introductionmentioning
confidence: 99%